Grozljivo v delih sodobne slovenske mladinske proze - Fink, Katarina (Revija za elementarno izobraževanje, 2010)
Horror in the works of contemporary Slovene writers for the young. In Slovene young adult literature, the genre of horror has been increasingly present from the 1990s onward. By reading horror literature, young readers experience oppressed mental states – terror and fear – which are otherwise negative, but they like to feel them when reading such literature. By doing this they willfully want to be overwhelmed with the feeling of threat due to the factors of unpleasantness, the unknown or unnatural factors which cannot be explained. But still, they are aware that it is fiction and feel safe. The elements of horror are present in numerous works of Slovene contemporary writers for the young as fragments or relatively shorter excerpts, but the basic perspective of the works is differently oriented. These works combine images of common (genre) characteristics; in the foreground, above everything else, is the battle between good and evil, the polarization of literary figures, definable boundaries between what is real and what is fictional from the reader’s experiences and the point of view of the emotional response as a cognitive feature based on the narrative procedure of presenting fictitious and traditional fairy-type narrative texts. All the literary texts represent the invasion of supernatural enemy forces, with which the authors gradually build the reader’s perception of terror. As a feature of horror, the literary figures are presented contrastingly and identify any individuals that stand out; the figures are thrown into certain actions and have no influence on it. In contemporary Slovene prose for the young, a two-dimensional level is present: the switch and twist of unusual and miraculous occurrences. Linguistic techniques increase the level of experiencing horror among young readers with high sensual perceptibility. The works analyzed are from contemporary Slovene prose for the young and are a presentation of concrete examples and characteristics of placing elements of horror among literary works.